A Cost-effectiveness Analysis of Brentuximab Vedotin in Relapsed or Refractory Systemic Anaplastic Large Cell Lymphoma - Margaret Hux; Denise Zou; Esprit Ma; Peter Sajosi; Andreas Engstrom; Ross Selby; Eugene Benson; Andrew Briggs; Vijayveer Bonthapally (Journal of Health Economics and Outcomes Research)
# Objective To evaluate the cost-effectiveness of brentuximab vedotin in patients with R/R sALCL from a UK NHS perspective.